Smoke control in an underground car park with impulse ventilation - Aveiro, J. (2010)
The covered car parks need to have means of ventilation, natural or mechanical, that provide the exhaust of the combustion products released by the engines of the vehicles passing through and to control the smoke released by fire. In last years, a new mechanical ventilation system appeared, based on the use of axial ventilators (jet fans) suspended under the car park ceiling. Jet fans generate the momentum necessary to promote the internal ventilation flow. In this way, the inlets and outlets may be concentrated in some points of the underground car park. Due to the general geometry of car parking, the flow can be rather complex, so parameters like the jet fans position, orientation and velocities have to be carefully chosen [1; 2]. While widely accepted design recommendations for this kind of projects are missing, the use of CFD software, as complement and auxiliary tool in the evaluation of ventilation design, can be of great interest. In this context, CFD simulations were carried out, using a freeware code (the FDS - Fire Dynamics Simulator), to evaluate and confirm the performance of an existing ventilation system, installed in an underground car park, in a fire scenario. The CFD results were compared with experimental values.